Межа між фактом і вимислом у літературно-інформаційному жанрі повісті-репортажу (на матеріалі твору Юрія Мушкетика «Час звіра») - Ромас, Людмила; Romas, Ludmila (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто факт співіснування в одному тексті ознак жанру журналістики (репортаж) та літе¬ратурного жанру (повість) на матеріалі твору «Час звіра» сучасного українського письменника Юрія Мушкетика. Досліджено відображення двох реальностей: тієї, у якій існує автор, та тієї, у якій існує авторська свідомість. The article deals with the coexistence in the same text attributes of reporting (a genre of journalism) and lead (literary genre) on the material of «Time of the beast» of modern Ukrainian writer Yuriy Mushketik. We study display two realities: one in which the author lives, and one in which there is the author’s consciousness. Also, the problem of how certain boundaries between the real facts of life and fiction in the literary genre of novel-information-report form in the recipient understanding of the multifaceted problem raised by the writer, which is manifested in the structuring of copyright worldview. It is proved that the organic compound of two genres taken from journalism and literature, has enabled the author to create an artistic document where the information is true and much sharper than in the historical novels and stories, because it served an eyewitness.
The line Between Faction in the Literary Genre Novels and Information Reports (baSed on work Yuriy Mushketik «Time Beast»)
Keywords: історичний факт; письменницький вимисел; художня реальність; літературно-інформа¬ційний жанр; повість-репортаж; Юрій Мушкетик; historical fact; fiction writer; artistic reality; literary and informative genre novel; reportage; Yuriy Mushketik